Synthesis, Characterization, Molecular Docking, Thermal Degradation Studies and Biological Screening of N-[2-(Pyridin-4-ylcarbonyl)hydrazinyl]carbonothioylfuran-2-carboxamide and its Mn(II), Ni(II), Co(II), Cu(II) and Zn(II) Complexes - Yuvaraj, T.C.M.; Naik, P. Parameshwara; Krishnamurthy, G.; Venkatesh, T.V.; Shafeeulla, R. Mohammed; Manjuraj, T.; Venugopal, T.M. (Asian Journal of Chemistry, 2017)
N-[2-(Pyridin-4-ylcarbonyl)hydrazinyl]carbonothioylfuran-2-carboxamide and its complexes with Ni(II), Co(II), Cu(II), Zn(II) and Mn(II) ions have been synthesized. The structure of the synthesized compounds was elucidated by elemental analysis, conductivity measurements, UV-visible, FT-IR, 1H NMR, powder XRD and thermal analysis studies. Most of metal complexes have exhibit thermal degradation between 80-750 °C and the powder X-rays diffraction data suggest that all the synthesized metal complexes were in nano crystalline phase. The computational molecular docking has been studied using Hex molecular modeling package version 8.2. The three dimensional structure of E. coli MurBenzyme (PDB code 2MBR) was used in microbial activity. The metal complexes showed comparable E total values with the standard drug tetracycline. The antioxidant and antimicrobial activity of prepared compounds indicate agreeable results versus bacterial strains three Gram-positive bacteria; S. aureus, S. pyogenes and P. acnes and three Gram-negative bacteria; E. coli, K. terrigena and K. pneumonia. The antifungal activity gave good results against fungal strains C. albicans, C. neoformans and Trichosporon.